An Interactive Adaptive Learning System Based on Agile Learner-Centered Design - Battou, A.; Baz, O.; Mammass, D. (EAI Endorsed Transactions on Smart Cities, 2018)
Adaptive and interactive Learning concepts has apprehended the interest of educational actors and partners, especially in higher education. However, the implementation of those concepts has faced many challenges, particularly in Interactive Adaptive Learning Systems (IALS). The present paper aims to give the foundation of a framework for an IALS that gives extensive attention at each stage of the design process to the end-user: learners. The system proposed is based on balanced combination of Agile Learning Design and Learner-Centred Design to improve teaching effectiveness, facilitate learning among learners, encourage long life learning and maximize motivation as well as reducing the dropout rate.